Relationship Between Nonalcoholic Fatty Liver Disease and Arrhythmia on Electrocardiogram - Fanying GONG; Jingjing ZHOU; Fuming LIU; Hui HUANG (国际转化医学杂志（英文版）, 2019)
Objective: To investigate whether there is a correlation between nonalcoholic faty liver disease (NAFLD) and arrhythmia on electrocardiogram. Methods: A retrospective controlled study was performed on the electrocardiogram of 200 patients admited to our department of cardiology. The study excluded patients with smoking history, drinking history, congenital heart disease, and malignant tumors. According to the ultrasound examination criteria, NAFLD was diagnosed by abdominal ultrasound examination and electrocardiogram (ECG) examination, which was analyzed by cardiovascular experts to assess NAFLD and baseline characteristics, clinical features, drug use, and arrhythmia ECG changes by univariate logistic regression analysis. Multivariate logistic regression was used to determine whether NAFLD is one of the most important factors affecting arrhythmia. Results: Of the 200 patients, 116 were found to have NAFLD and 84 were without NAFLD. Among them, a total of 91 arrhythmias occurred in 76 patients, as follows: 30.2％ (23 cases) sporadic atrial premature beats, 51.3％ (39 cases) occasional ventricular premature beats, 19.7％ (15 cases) frequent ventricular premature beats, 10.5％ (8 cases) multi-source atrial premature beats complicated with short-term atrial tachycardia, 3.9％ (3 cases) atrial fibrillation and 3.9％ (3 cases) short-term ventricular tachycardia. Univariate logistic regression analysis found that including gender (male), coronary artery disease, hypertension, diabetes, arrhythmia ECG changes (occasion of premature atrial premature beats, occasional premature ventricular contractions, frequent ventricular premature beats, multi-source atrial premature beats Short-term atrial tachycardia, atrial fibrillation, and short-term ventricular tachycardia were positively correlated with NAFLD. Five risk factors for the following arrhythmias were identified using multivariate regression model analysis: NAFLD (OR = 2.35; 95％CI: 1.46-3.83, P < 0.001), coronary artery disease (OR = 2.56; 95％CI: 1.58-4.11, P < 0.001), hypertension (OR = 2.98; 95％CI: 1.52-6.31, P < 0.001), male (OR = 1.78;95％CI: 1.18-2.70, P < 0.001) and age (OR = 1.04; 95％CI: 1.02-1.06, P < 0.001). Conclusion: NAFLD is associated with arrhythmia ECG changes.